PENGARUH PROGRAM TAHFIDZ QUR’AN TERHADAP PEMBENTUKAN KARAKTER ISLAMI PESERTA DIDIK DI MADRASAH ALIYAH NEGERI (MAN) 4 KARAWANG - Sumiyati, Aan (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
In this research there are two variables consisting of the tahfidz Qur'an program and the Islamic character of students, so the aim of this research is to present an overview of the tahfidz Qur'an program, the Islamic character of students, and the influence between the two. in a correlational relationship. The population in this study were students at MAN 4 Karawang with a sample size of 35 people. Meanwhile, the method used in this research is a correlational method with a quantitative approach. This method was used to identify the influence of the tahfidz Qur'an program on the formation of students' Islamic character at MAN 4 Karawang. The results of this research show that 17% of the tahfidz qur'an program is in the low category, 69% is in the medium category and 14% is in the high category so it can be concluded that the average implementation of the tahfidz qur'an program at MAN 4 Karawang is in the medium category. As for the Islamic character formation of students, 9% are in the low category, 80% are in the medium category and 11% are in the high category, so it can be concluded that the average Islamic character formation of MAN 4 Karawang students is in the medium category. Based on SPSS in the coefficients table, it can be seen that the significance value (sig.) is 0.001 < 0.05 so it can be concluded that Ho is rejected and Ha is accepted. This means